Wilcoxon Match Pairs Test To Know The Application Of Rolling Ball Media On Learning Outcomes: Uji Pasangan Wilcoxon untuk Mengetahui Penerapan Media Bola Berputar pada Hasil Belajar - Dian Kusuma Wardani; M Aliyul Wafa; Evy Dwi Andriani (Chalim Journal of Teaching and Learning, 2025)
Results This research aims to determine student learning outcomes by applying the Rolling Ball learning media in fiqh subjects and as an alternative for teachers in an effort to provide understanding to students and improve student learning outcomes in fiqh subjects. The method used in this research is quantitative. Data collection instruments through observation, interviews, pre-test and post-test questions. The subjects taken in this research were the MA Al-Bayruni school class XI-IPA 2 Sambong. The results of the data normality test obtained values from the pre-test and post-test results that were greater than 0.05, namely 0.091>0.05 and 0.026>0.05, it can be concluded that the data is normally distributed. The results of the analysis using the t test obtained a result of 0.008 < 0.05 so it can be said that there is an influence from the application of the Rolling Ball learning model to student learning outcomes.